Assessment of school based management committees' involvement in managing public primary schools in Maiduguri Metropolis, Borno State, Nigeria - Ali, Muhammad; Sani, Maryam (Kashere Journal of Education, 2023)
The study assessed school based-management committees' (SBMCs') involvement in Managing public primary schools in Maiduguri Metropolis Borno State, Nigeria. The objectives of the study were to assess: SBMCs' involvement in provision of educational resources; maintenance of educational resources and SBMCs' involvement in maintenance of discipline among pupils in public primary schools in Maiduguri Metropolis, Borno State, Nigeria. Three research questions were answered. Survey research design was adopted for the study. Simple random sampling technique was used to select 19 head teachers out of the population of 39 head teachers of public primary schools in Maiduguri Metropolis, Borno State. Questionnaire was used for data collection. The questionnaire was validated and pilot tested. The validity index yielded a coefficient of 0.78, while the reliability index yielded a coefficient of 0.72. Mean and standard deviation were used to analyze the data. The findings of the study revealed that there were passive SBMCS' involvement in the provision of educational resources, there were active SBMCS' involvement in the maintenance of educational resources, as well as active involvement in maintenance of discipline among pupils in public primary schools in Maiduguri Metropolis Borno State, Nigeria. Based on the findings of the study, it was recommended that government should create awareness to enlighten parents, alumni, community leaders, religious leaders on the importance attached to SBMCs involvement in provision and managing educational resources as well as maintenance of discipline among pupils in public primary schools in Maiduguri Metropolis, Borno State, Nigeria.